Hirschsprung Disease Diagnosis: Calretinin Marker Role in Determining the Presence or Absence of Ganglion Cells - Nasser Rakhshani; Mohammadreza Araste; Farid Imanzade; Mahshid Panahi; Fahimeh Safarnezhad Tameshkel; Masoud Reza Sohrabi; Mohammad Hadi Karbalaie Niya; Farhad Zamani (Iranian Society of Pathology, 2016)
Background: Hirschsprung disease is a complex genetic disorder of the enteric nervous system (ENS), often called congenital aganglionic megacolon and characterized by the absence of enteric neurons along a variable length of the intestine. The definitive diagnosis of Hirschsprung disease relies on histologic and/or histochemical staining of sections from suction rectal biopsies. Calretinin immunohistochemistry (IHC) may be a useful in its diagnosis. This study aimed to proof the usefulness of immunohistochemical staining for calretinin in rule out of Hirschsprung disease. Methods: Paraffin blocks and slides were retrieved from the pathology archives of Ali Asghar Hospital, Tehran, Iran from 2007 to 2011 with pathology report based on the presence (14 patients) or absence (70 patients) of ganglion cells and transitional zone anatomical region (10 patients). Slides were stained with hematoxylin and eosin method to confirm the initial diagnosis was verification again. After preparing the slides, they were stained by IHC for calretinin. Then, the results were analyzed using SPSS software. Results: In most patients, IHC for calretinin provided highly compatible results with hematoxylin-eosin findings in diagnosis of Hirschsprung disease. The values of specificity and accuracy between calretinin and standard histology (H&E) compared by the Fisher exact test declared calretinin presented significantly higher specificity and accuracy values than H&E staining (P <0.0001). Conclusion: Calretinin IHC overcomes most of the difficulties encountered using the histology hematoxylin-eosin. Then, IHC for calretinin is a good ancillary method used by pathologists in diagnosis of Hirschsprung disease.